On end-to-end scheduling in wireless cellular networks - Saad, Walid (2008)
Wireless cellular networks are required to meet the stringent QoS requirements of emerging data services. To efficiently utilize the available radio resources, we propose a new resource allocation algorithm for services that require end-to-end guarantees. Unlike existing literature that mainly focuses on downlink only or uplink only scheduling algorithms, the proposed algorithm aims at ensuring an end-to-end utility value reflecting end-to-end QoS in terms of delay and channel quality. By jointly considering the time varying channel conditions in both uplink and downlink directions, the proposed end-to-end scheduling algorithm achieves an increased number of active connections and a lower packet drop in comparison to other schemes. These gains are achieved with a tradeoff cost in terms of complexity and signaling overhead. For overhead reduction, we propose an implementation over clusters within the network.